Can MRI Distinguish between a Partial Anterior Cruciate Ligament (ACL) Tear and a Normal ACL? - Mikashima, Yoshinori; Tomatsu, Taisuke; Miyawaki, Motoko; Koshiishi, Takeshi; Takagi, Tadashi; Ikari, Katsunori; Momohara, Shigeki (International Journal of Orthopedics and Rehabilitation, 2016)
Objective: The purpose of this study was to determine whether Magnetic resonance imaging (MRI) can distinguish between a partial anterior cruciate ligament (ACL) tear and a normal ACL. Materials and Methods: MR images of 20 patients with an arthroscopically confirmed partial ACL tear were retrospectively interpreted by the author, comparing with normal ACLs. Results and Discussion: All knees with a partial ACL tear had a continuous band of low signal, of which 15 had no increased signal intensity on proton density-weighted images. MRI could not distinguish between a partial ACL tear and a normal ACL. Orthopedic surgeons had better consider an ACL tear when a patient has traumatic hemarthrosis or anxiety provoked by the sensation of the knee ‘going out’ or ‘giving way’ during the pivot shift test, even if the ACL has a continuous band of low signal on the oblique sagittal view on MRI.